Pretreatment of kenaf (Hibicus cannabinus L.) core fibre for fermentable sugar and lactic acid production - Ng, Sim Hong (2012)
Kenaf (Hibiscus cannabinus L.) core which is mainly used for low range products contains high cellulose content (46.9%) possesses great potential for fermentable sugar production. Kenaf core can be converted into lactic acid (LA) through enzymatic hydrolysis and fermentation process. However, pre-treatment is essential prior to enzymatic hydrolysis for higher fermentable sugar yield. In this study, three types of pre-treatments were applied: i) Physical pre-treatment (hammer milling,HM); ii) Physical and thermal pre-treatment (HMTH) iii) Physical and chemical pretreatment (HMCH). The cellulase enzyme from Trichoderma reesei was used to hydrolyze the pre-treated kenaf core. Lactic acid bacteria, Lactobacillus delbrueckii,Lactoccocus lactis NZ9000 and Lactoccocus lactis MG 1363 were used for fermentation in batch cultivation for 24 hours using kenaf core hydrolysate. The chemical composition of kenaf core was analyzed according to TAPPI Standard methods and the concentration of fermentable sugar and LA yield was analyzed using HPLC. The study showed that NaOH pre-treated kenaf core recorded the highest alpha cellulose content (91.5%) at >80 mesh among the pre-treatments. After hydrolysed by cellulose, NaOH pre-treated kenaf core generated the highest amount of glucose (11.64 g/L) compared to the untreated (40-60 mesh) kenaf core (0.04 g/L). In fermentation by L. delbrueckii using kenaf core hydrolysate prepared from 2.0 mL enzyme loading as a substrate, the highest lactic acid production with 11.80 g/L was obtained at 12th hour of cultivation with 2.86 g/L of cell growth. However, the maximum concentration of 12.78 g/L of lactic acid was obtained with 3.05 g/L of maximum cell growth at 24 hours of cultivation. L. delbrueckii recorded the highest cell efficiency to produce lactic acid at 4.24 g/g, and therefore, recorded the highest productivity at 0.533 g/L/h. The results show that NaOH pre-treated kenaf core is the most suitable pre-treatment to obtain the highest glucose yield by increasing the alpha cellulose content. Subsequently, L. delbrueckii is the most suitable lactic acid bacteria to produce lactic acid from kenaf core hydrolysates and can be used as a potential lactic acid bacteria for other lignocellulose bioconversion to lactic acid.